A high-resolution late Holocene lake isotope record from Turkey and links to North Atlantic and monsoon climate - Jones, Matthew D.; Roberts, C. Neil; Leng, Melanie J.; Türkeş, Murat (Geological Society of America, 2006)
A high resolution proxy record of precipitation and evaporation variability through the past 1700 yr from δ18O analysis of a varved lake sequence from central Turkey shows rapid shifts between dry periods (AD 300–500 and AD 1400–1950) and wetter intervals (AD 560–750 and AD 1000–1350). Changes are consistent with changes in instrumental and proxy records of the Indian monsoon, dry summers in the Eastern Mediterranean being associated with periods of enhanced monsoon rainfall. In addition major shifts in the record are coherent with changes in North Atlantic winter climate with cold, wet periods in the Alps occurring at times of dry Turkish climate.